2011
DOI: 10.1002/j.2161-0029.2011.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Infusing Multicultural and Social Justice Competencies Within Counseling Practice: A Guide for Trainers

Abstract: In light of rapidly changing demographics within the United States, counselors are challenged to provide culturally responsive services to facilitate optimal client functioning. This article highlights recommended training strategies within a developmental framework to promote multicultural and social justice competencies for trainers of mental health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Most of the studies were done in high-income countries, most in the USA or Canada (Bakshi et al., 2015 ; Boutain, 2008 ; Crawford et al., 2017 ; Dharamsi et al., 2010 ; Flatt-Fultz & Phillips, 2012 ; Gonzalez et al., 2015 , 2020 ; Jindal et al., 2022 ; Knaak, 2018 ; Lax et al., 2019 ; Sukhera et al., 2020 ; Tucker et al., 2020 ; White-Davis et al., 2018 ; Zäske et al., 2014 ). Four studies included data from middle and low-income countries (Ezedinachi et al., 2002 ; Geibel et al., 2017 ; Potts et al., 2022 ; Uys et al., 2009 ) In terms of participants, 24 studies focused on healthcare students, be that nursing or medicine, describing programs added to teaching curriculums at universities (Allen et al., 2013 ; Bakshi et al., 2015 ; Boutain, 2008 ; Burdett et al., 2010 ; Crawford et al., 2017 ; DallaPiazza et al., 2018 ; DeLashmutt & Rankin, 2005 ; Dharamsi et al., 2010 ; Gonzalez et al., 2015 , 2020 ; İnan et al., 2019 ; Jones, 2000 ; Jindal et al., 2022 ; Lax et al., 2019 ; Mason & Miller, 2006 ; McAllister, 2008 ; O Carroll & O’Reilly, 2019 ; Potts et al., 2022 ; Shah et al., 2014 ; Sheely-Moore & Kooyman, 2011 ; Tucker et al., 2020 ; Üstün & İnan, 2018 ; Wagaman et al., 2019 ; Werkmeister Rozas & Garran, 2016 ). A small proportion of studies focused on participants with work experience, such as therapists or specialist mental healthcare staff (Ezedinachi et al., 2002 ; Fisher et al., 2017 ; Fisher-Borne, 2009 ; Flatt-Fultz & Phillips, 2012 ; Knaak, 2018 ; Li et al., 2015 , 2013 ; Nelso...…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were done in high-income countries, most in the USA or Canada (Bakshi et al., 2015 ; Boutain, 2008 ; Crawford et al., 2017 ; Dharamsi et al., 2010 ; Flatt-Fultz & Phillips, 2012 ; Gonzalez et al., 2015 , 2020 ; Jindal et al., 2022 ; Knaak, 2018 ; Lax et al., 2019 ; Sukhera et al., 2020 ; Tucker et al., 2020 ; White-Davis et al., 2018 ; Zäske et al., 2014 ). Four studies included data from middle and low-income countries (Ezedinachi et al., 2002 ; Geibel et al., 2017 ; Potts et al., 2022 ; Uys et al., 2009 ) In terms of participants, 24 studies focused on healthcare students, be that nursing or medicine, describing programs added to teaching curriculums at universities (Allen et al., 2013 ; Bakshi et al., 2015 ; Boutain, 2008 ; Burdett et al., 2010 ; Crawford et al., 2017 ; DallaPiazza et al., 2018 ; DeLashmutt & Rankin, 2005 ; Dharamsi et al., 2010 ; Gonzalez et al., 2015 , 2020 ; İnan et al., 2019 ; Jones, 2000 ; Jindal et al., 2022 ; Lax et al., 2019 ; Mason & Miller, 2006 ; McAllister, 2008 ; O Carroll & O’Reilly, 2019 ; Potts et al., 2022 ; Shah et al., 2014 ; Sheely-Moore & Kooyman, 2011 ; Tucker et al., 2020 ; Üstün & İnan, 2018 ; Wagaman et al., 2019 ; Werkmeister Rozas & Garran, 2016 ). A small proportion of studies focused on participants with work experience, such as therapists or specialist mental healthcare staff (Ezedinachi et al., 2002 ; Fisher et al., 2017 ; Fisher-Borne, 2009 ; Flatt-Fultz & Phillips, 2012 ; Knaak, 2018 ; Li et al., 2015 , 2013 ; Nelso...…”
Section: Resultsmentioning
confidence: 99%
“…This would involve going beyond acknowledgment of systemic injustices and adopting a professional responsibility to affect change at the societal level (Alegria et al, 2022). Scholars have argued for clinicians to engage in advocacy work outside of the therapy room, educating themselves on the structural forces that influence their marginalized clients and then supporting collective action (e.g., community service, campaigning, protesting) aimed at correcting these injustices (Kirmayer et al, 2018, Sheely & Kooyman, 2011. Clinicians in training may benefit from instruction that bridges psychological practice and social justice advocacy, preparing them to aid marginalized individuals while becoming agents of change that can help to ameliorate these oppressive environments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review [28] of the feasibility and effectiveness of training in health advocacy, anti-stigma competency or related skills for health professionals retrieved 39 studies, three of which reported interventions for mental health care professionals [21,[29][30][31]. Programme content varied widely; some covered mainly interpersonal stigma reduction, others focusing on social determinants of health and some included health advocacy at the structural level.…”
Section: Introductionmentioning
confidence: 99%